ANALISIS MODEL PENTANAHAN MENARA BTS (BASED TRANSCEIVER STATION) DENGAN TAHANAN PENTANAHAN MODEL BC SPIRAL - Irawati, Irawati; Ismuharam, Ismuharam; Sumarno, Edy; Gazali, Ria; Kartikasari, Deasy (Institut Teknologi dan Bisnis Swadharma, 2025)
Insufficient grounding strength during operation may cause malfunction and damage to electronic devices. There is an increased risk of arrhythmia due to lightning strikes. The smaller the number found at each grounding angle, the more stable the grounding system is. The research aims to obtain as much grounding as possible. The technique used to reduce the amount of grounding output is to place electrodes in the ground. The technique will help increase the efficiency of the grounding system. In addition, measuring soil characteristics is very important to understand the value of the type of resistance, which then influences the overall grounding resistance. The strength of the grounding is greatly influenced by its type, so it is necessary to carry out a thorough analysis based on soil characteristics, which is usually carried out in constructing BTS towers with the BC Spiral model. Based on the analysis results, the resistance of the BTS model to abrasion is 0.26 ohms, while the PUIL 2000 standard is less than 2 ohms. The measurements on the BTS model using the BC Spiral model are close to the expected results. The results of this research provide a positive picture of the effectiveness of the grounding system implemented, and this conclusion can be used to ensure good protection of electronic devices on the BTS tower from potential damage due to lightning strikes. Continuously update safety standards and carry out routine maintenance to ensure grounding system performance remains optimal.Kekuatan pentanahan yang tidak memadai selama pengoperasian dapat menyebabkan kegagalan fungsi dan kerusakan pada perangkat elektronik. Resikonya akan terjadi peningkatan aritmia akibat sambaran petir. Semakin kecil angka yang dapat ditemukan pada setiap sudut pentanahan maka semakin stabil sistem pembumiannya. Tujuan penelitian adalah memperoleh pentanahan sebanyak-banyaknya. Teknik yang digunakan untuk mengurangi jumlah hasil pentanahan adalah dengan menempatkan elektroda di dalam tanah. Hal ini akan membantu meningkatkan efisiensi sistem pembumiannya. Selain itu, pengukuran karakteristik tanah sangat penting untuk memahami nilai jenis tahanannya, yang kemudian memengaruhi tahanan pentanahan secara keseluruhan. Kekuatan pentanahan sangat dipengaruhi oleh jenisnya, sehingga perlu dilakukan analisis menyeluruh berdasarkan karakteristik tanah, yang biasa dilakukan pada pembangunan menara BTS dengan model BC Spiral. Berdasarkan hasil analisa, ketahanan model BTS terhadap abrasi adalah 0,26 ohm, sedangkan standar PUIL 2000 kurang dari 2 ohm. Hasil pengukuran yang dilakukan pada model BTS dengan menggunakan model BC Spiral sudah mendekati hasil yang diharapkan. Hasil penelitian ini memberikan gambaran positif tentang keefektifan sistem pentanahan yang diterapkan, dan kesimpulan ini dapat digunakan untuk memastikan perlindungan yang baik terhadap perangkat elektronik di tower BTS dari potensi kerusakan akibat sambaran petir. Perbaharui terus standar keamanan dan lakukan pemeliharaan rutin untuk memastikan kinerja sistem pentanahan tetap optimal.